Ultrafast and low-cost preparation of Mg2(Si0.3Sn0.7)1−ySby with superior thermoelectric performance by self-propagating high-temperature synthesis. (15th March 2019) - Zhang, Qiang; Su, Xianli; Yan, Yonggao; Zheng, Yun; Liu, Wei; Tang, Xinfeng
Abstract: The innovation of fabrication method is definitely playing a vital role, not only in tuning various material properties, but in facilitating the future commercial applications. Herein, Mg2 (Si0.3 Sn0.7 )1−y Sby solid solutions were synthesized by a new, ultrafast and low-cost self-propagating high-temperature synthesis (SHS) method, enabling the large-scale preparation of these materials. The obtained sample exhibits decent thermoelectric performance with a figure of merit, ZT, of above 1.1 and a high average ZT of 0.95. Since SHS method shows the impressive merits of high energy-efficiency, short time-consumption, and the large-scale productivity, this technique should be greatly accentuated for the other potential functional materials. Graphical abstract: Sb doped Mg2 (Si0.3 Sn0.7 )1−y Sby solid solutions were prepared by ultrafast and low-cost self-propagating high-temperature synthesis (SHS) combined with plasma activated sintering (PAS), exhibiting superior thermoelectric figure of merit ZT including peak ZT peak and average ZT av . Unlabelled Image